SELF-EDUCATION AND SELF-IMPROVEMENT - Raximjanov Masrur Nugmanovich (Galaxy International Interdisciplinary Research Journal, 2021)
In order for a teacher to educate himself, he must first study himself in depth, be able to see the successes and shortcomings of his work. It is also necessary for self-study and understanding of the other person. It is impossible to study oneself as a person without learning other achievements and comparing oneself with others. Self-awareness, a feature of self-assessment, is formed in the process of interacting with other people, during joint activities.